Perfil sociodemográfico materno em pacientes Near Miss neonatal de uma maternidade de alto risco - Simões, Fernanda Monteiro Batista (2018)
Reducing infant mortality and improving the health of pregnant women are challenges to maternal and child health. The use of the concept of near miss neonatal (NMN) has been shown as an important tool in qualifying the factors that influence infant morbidity and mortality. It is well established in the literature that gestational factors related to childbirth and newborn care have a strong impact on the outcome of maternal and child health, but there are not many studies on maternal socio-demographic influence in these outcomes. The present study aims to describe the sociodemographic profile of mothers whose newborns were considered near miss neonatal. A cross-sectional study nested in a case-control study was carried out at a high risk maternity hospital in Aracaju, Sergipe, Brazil. Cases of NMN were identified and maternal sociodemographic profile data were collected through interviews and data collection. Between March and September 2015, 3270 medical records were analyzed and 130 cases of NMN were identified, of which 5 were discarded due to collection error. Of the results found, part was of urban area, with an average age of 25.8 years, brown, less than 8 years of study and married or in stable union. In addition, most were unemployed, had a monthly income of up to three minimum wages and did not receive government aid. Although this article has not used analytical formulas, the data call attention to the social panorama that these women are subjected, since social development is one of the predictors of public health.